UPAYA PRAPERADILAN ATAS PENGHENTIAN PENYIDIKAN TERHADAP TINDAK PIDANA PEMALSUAN SURAT MENGANDUNG OBSCUUR LIBEL - Riswan Munthe; Yusuf Hanafi Pasaribu; Sri Hidayani (Jurnal Yuridis, 2024)
The aim of this research is only to focus on discussing the authority of pre-trial institutions regarding the termination of investigations carried out by the Police regarding criminal acts of document forgery and procedures for whether or not the termination of an investigation (SP3) is valid based on evidence as well as pre-trial applications containing obscuur libel based on decision Number 43/Pid. Pra/2023/PN Mdn. The research method used is normative legal research, which refers to library materials or secondary data. The collection of materials used is literature study based on books, journal articles and field studies by taking court decision data, then the data is analyzed qualitatively. The results of this research found that the pre-trial authority to terminate investigations carried out by the Police regarding criminal acts of forgery of documents, namely pre-trial in accordance with the provisions of Article 1 point 10 of the Criminal Procedure Code and Article 77 of the Criminal Procedure Code and based on the decision of the Constitutional Court of the Republic of Indonesia Number 21/PUU-XII/2014 has been given three new pretrial object authority, namely the determination of suspects, search and confiscation. The procedure for whether to stop an investigation (SP3) is valid or not if it refers to the provisions of Article 109 paragraph (2) of the Criminal Procedure Code, namely stopping the investigation because there is not enough evidence or the incident turns out not to be a criminal act or the investigation is stopped by law. Meanwhile, the pretrial petition containing obscuur libel in decision Number 43/Pid.Pra/2023/PN Mdn, based on the judge's considerations in the posita and petitum of the applicant's pretrial petition, has conflicted with one another, so that the judge's obscuur libel petition contains formal defects.